2020
DOI: 10.2147/ndt.s236541
|View full text |Cite
|
Sign up to set email alerts
|

<p>Commensal Microbiota Regulation of Metabolic Networks During Olfactory Dysfunction in Mice</p>

Abstract: Introduction: Recently, an increasing number of studies have focused on commensal microbiota. These microorganisms have been suggested to impact human health and disease. However, only a small amount of data exists to support the assessment of the influences that commensal microbiota exert on olfactory function. Methods: We used a buried food pellet test (BFPT) to investigate and compare olfactory functions in adult, male, germ-free (GF) and specific-pathogen-free (SPF) mice, then examined and compared the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For patients with cardiopulmonary failure, glycerolipid metabolism, aminoacyl-tRNA biosynthesis, and glutathione metabolism are all related metabolic pathways implicated in oxidative stress, lactic acidosis, and mitochondrial dysfunction [24]. In addition, arginine plays a key role in regulating cardiovascular dysfunction [25-28]. Both hypoxanthine and guanine are related to purine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with cardiopulmonary failure, glycerolipid metabolism, aminoacyl-tRNA biosynthesis, and glutathione metabolism are all related metabolic pathways implicated in oxidative stress, lactic acidosis, and mitochondrial dysfunction [24]. In addition, arginine plays a key role in regulating cardiovascular dysfunction [25-28]. Both hypoxanthine and guanine are related to purine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…According to meticulous analysis, the abundances of 38 metabolites were identified as showing significant differences between germ-free mice and specific pathogen-free mice (Wang et al, 2020). In another notable study, Casadei et al found that germ-free zebrafish exhibited similar effects, as their OE displayed evident pseudostratification defects (Casadei et al, 2019).…”
Section: Influence On Olfactory Perceptionmentioning
confidence: 99%
“…In addition, the metabolic signatures of olfactory bulbs underwent significant alterations. According to meticulous analysis, the abundances of 38 metabolites were identified as showing significant differences between germ‐free mice and specific pathogen‐free mice (Wang et al., 2020). In another notable study, Casadei et al.…”
Section: The Role Of the Oral Microbiota In Aroma Release And Perceptionmentioning
confidence: 99%
“…Although the exact mechanisms involved remain unclear, accumulating evidence has demonstrated that gut microbiota dysbiosis can adversely affect behavior and neural biochemistry through the microbiota-gut-brain axis ( Cryan & Dinan, 2012 ; Fung et al, 2017 ; Long-Smith et al, 2020 ). In previous studies, we showed that the gut microbiota modulates gene transcription and protein expression ( Chen et al, 2019 ; Liu et al, 2020 ; Rao et al, 2021 ; Zeng et al, 2016 ; Zhou et al, 2020 ) and drives metabolic alterations in the brains of rodents and nonhuman primates ( Li et al, 2018a ; Wang et al, 2020a ; Zheng et al, 2021 ). The gut microbiota varies with lifecycle and exerts profound influences on the host ( Yang et al, 2022 ), with bacterial infection found to precipitate stress-induced memory dysfunction ( Gareau et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Germ-free (GF) animals, which lack microbiota and are free from bacterial contamination, serve as suitable models for exploring host responses to disordered, normal, or absent flora. GF mice have been an invaluable tool for investigating microbiota-host interactions ( Cryan & Dinan, 2012 ; Cryan et al, 2019 ; Foster & McVey Neufeld, 2013 ; Long-Smith et al, 2020 ; Zheng et al, 2019 ) and exhibit cognitive deficits, altered sociability, and modifications in neurogenesis, neurotransmitter, synapse, and neuronal activity-related genes ( Cryan et al, 2019 ; Luczynski et al, 2016 ; Schretter, 2020 ; Wang et al, 2020a ). We have also previously identified decreased depressive and anxiety-like behavior in GF mice accompanied by molecular and neurochemical changes ( Chen et al, 2017b , 2019 ; Zeng et al, 2016 ; Zheng et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%